2022
DOI: 10.1021/acsami.2c07252
|View full text |Cite
|
Sign up to set email alerts
|

Ga-Promoted CuCo-Based Catalysts for Efficient CO2 Hydrogenation to Ethanol: The Key Synergistic Role of Cu-CoGaOx Interfacial Sites

Abstract: Currently, direct catalytic CO2 hydrogenation to produce ethanol is an effective and feasible way for the resource utilization of CO2. However, constructing non-precious metal catalysts with satisfactory activity and desirable ethanol selectivity remains a huge challenge. Herein, we reported gallium-promoted CuCo-based catalysts derived from single-source Cu-Co-Ga-Al layered double hydroxide precursors. It was manifested that the introduction of Ga species could strengthen strong interactions between Cu and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…It was reported that surface oxygen vacancies are responsible for improving CO 2 adsorption. 60 Therefore, for present CoFe/ ZrO 2 catalysts, the surface-dominant FeO x component with high concentrations of oxygen vacancies may be the main active species for CO 2 hydrogenation.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…It was reported that surface oxygen vacancies are responsible for improving CO 2 adsorption. 60 Therefore, for present CoFe/ ZrO 2 catalysts, the surface-dominant FeO x component with high concentrations of oxygen vacancies may be the main active species for CO 2 hydrogenation.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Zhang et al developed a Ga-promoted CuCo catalyst for ethanol production by CO 2 hydrogenation, 173 Overall, despite researchers' best efforts to optimize ethanol production, the yield remains quite low, failing to reach 10%. Ethanol production by CO 2 hydrogenation is thus a complex task and requires substantial purification work to obtain a refined product, leading to significantly higher costs than standard ethanol production methods.…”
Section: Ethanol Synthesismentioning
confidence: 99%
“…Zhang et al developed a Ga-promoted CuCo catalyst for ethanol production by CO 2 hydrogenation, using a CuCoGaAl layered double hydroxide precursor. Using a Ga/Co molar ratio of 0.4, they were able to achieve 23.8% ethanol selectivity and 17.8% CO 2 conversion, outperforming most noble-metal catalysts previously explored in literature.…”
Section: Thermochemical Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical conversion of CO 2 to high-value-added carbon compounds is an effective way to achieve the carbon cycle. The thermal catalytic CO 2 hydrogenation reaction has evoked considerable attention, which produces various chemicals including CO, CH 4 , CH 3 OH, olefins, etc. Among the reported process, the CO 2 methanation reaction (CO 2 + 4H 2 ↔ CH 4 + 2H 2 O) has been considered a promising way since CH 4 can be directly stored and distributed using already existing natural gas pipeline networks. This is a thermodynamically exothermic reaction (Δ G 298K = −113 kJ·mol –1 and Δ H 298K = −165 kJ·mol –1 ), and a low reaction temperature is favorable to reduce the formation of the byproduct CO . Although great advances have been achieved in noble-metal catalysts (e.g., Ru, , Rh, , and Pd) at low temperatures, they are limited by the low reserve and high price.…”
Section: Introductionmentioning
confidence: 99%